Efficacy and safety of Chinese botanical drug Si Shen Wan in irritable bowel syndrome: a meta-analysis and trial sequential analysis of randomized controlled trials - Liu, Qian; Shi, Zongming; Jiang, Yang; Zhang, Tao; Du, SiJing; Gao, Yemei (Frontiers in Pharmacology, 2025)
Background and ObjectivesIrritable bowel syndrome (IBS) is one of the most common functional gastrointestinal disorders (FGIDs), characterized by complex pathogenesis, prolonged disease duration, frequent recurrence, and a significant impact on patients’ quality of life. Si-Shen-Wan (SSW), a renowned traditional Chinese medicine formula, is widely recognized for its efficacy in managing gastrointestinal symptoms, particularly diarrhea, and is commonly used to treat diarrhea-predominant IBS (IBS-D). This study utilized a meta-analysis to evaluate the efficacy and safety of SSW in the treatment of IBS-D.MethodsA comprehensive search for randomized controlled trials (RCTs) was conducted across seven databases from their inception to 31 October 2024. The analysis included outcomes such as efficacy rate, overall symptom score, abdominal pain score, diarrhea score, abdominal distension score, loss of appetite score, recurrence rate, and adverse events. Meta-analyses were performed using either a random-effects or fixed-effects model. Trial sequential analysis (TSA) was applied to estimate the sample size and validate the robustness of the meta-analysis.ResultsA total of 34 RCTs involving 2,976 participants met the inclusion criteria. The findings demonstrated that SSW alone (RR = 1.28; 95% CI: 1.21, 1.34; P < 0.00001) or combined with biomedicine (RR = 1.26; 95% CI: 1.18, 1.35; P < 0.00001) significantly improved treatment efficacy compared to biomedicine alone. SSW also reduced the overall symptom score (SMD = −1.06; 95% CI: −1.50, −0.61; Z = 4.66; P < 0.00001) and alleviated key symptoms, including abdominal pain (MD = −0.66; 95% CI: −0.76, −0.56; Z = 12.99; P < 0.00001), diarrhea (MD = −0.69; 95% CI: −0.81, −0.56; Z = 10.82; P < 0.00001), abdominal distension (MD = −0.65; 95% CI: −1.06, −0.24; Z = 3.13; P = 0.002), and loss of appetite (MD = −0.55; 95% CI: −0.66, −0.44; Z = 9.80; P < 0.00001). The recurrence rate was also significantly reduced (RR = 0.40; 95% CI: 0.29, 0.55; P < 0.00001). Additionally, SSW combined with moxibustion—a traditional Chinese medicine therapy integrating internal and external treatments—also further improved treatment outcomes (RR = 1.22; 95% CI: 1.08, 1.37; P = 0.0001). This combination effectively reduced abdominal pain (MD = −0.42; 95% CI: −0.81, −0.04; Z = 2.17; P = 0.03), diarrhea (MD = −0.41; 95% CI: −0.64, −0.17; Z = 3.41; P = 0.0006), abdominal distension (MD = −0.40; 95% CI: −0.69, −0.11; Z = 2.67; P = 0.008), and loss of appetite (MD = −0.30; 95% CI: −0.49, −0.10; Z = 2.93; P = 0.003). Safety analysis revealed a high level of safety for SSW and SSW combined with moxibustion, with no serious adverse events reported in any of the included trials. TSA confirmed an adequate sample size for the primary outcome, supporting the efficacy of SSW in IBS-D treatment.ConclusionSSW, either used alone or combined with moxibustion, is effective in alleviating IBS-D symptoms and reducing recurrence rates, making it a potentially beneficial intervention. However, certain limitations remain in the overall quality of the current studies, including relatively small sample sizes, insufficiently long follow-up periods, and the absence of a double-blind design. Future research should emphasize the design and implementation of high-quality, long-term, randomized, double-blind clinical trials to further enhance the reliability and external applicability of the research findings.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=597979, identifier CRD42024597979.